(untitled) (Advances in Applied Mathematics and Mechanics, 2010)
Optimum design of structures is achieved by genetic algorithm. The evolutionary algorithm is employed to design structures. The method improves the computing efficiency of the large-scale optimization problems and enhances the global convergence of the design process. The loads are considered as earthquake loads. A time history analysis is carried out for the dynamic analysis. To decrease the computational work, a wavelet transform is used by which the number of points in the earthquake record is reduced. A reverse wavelet transform is also employed to reconstruct the functions under consideration in the time domain. A number of space structures are designed for minimum weight and the results are compared with exact dynamic analysis.